دراسة العلاقة بين اشكال السرعة بكرة القدم لدى لاعبي الرديف لنادي الزرواء الرياضي بكرة القدم: Studying The Relationship Between The forms of speed of Soccer In The Players of the Reserve for Al – Zawra Sports Club Soccer - Fadl, Abdul Karim; Falh, Rswal (Journal of Physical Education, 2017)
The importance of research is to know the relationship between the forms of speed, in order to reach the best levels that help the player to invest opportunities in the course of matches, which require a link between this speed to reach the ideal performance, and the researcher is one of the football players and through the follow-up field and watching the matches Note that there is weakness in some types of speed (kinetic - transitional - response speed) in the players of the reserve for Al - Zawra sports club and because these forms are very important and must have the ability to connect these forms of the researcher to consider the study of the relationship between some Among the forms of speed (speed of movement - speed of transit - response speed) in the players of the reserve for Al-Zawra football club. The objective of the research is to Identify the relationship between the forms of speed (motor speed - the speed of speed - the speed of response) to the football players of the reserve for Al-Zawra football club. The researcher used the descriptive method in the method of associative relations, and the sample was chosen by the intentional way and from the club of Al-Zawra sports club. The researcher conducted the main experiment on 20 players on the day of the test using special tests for speed forms (speed, Response). The researcher used the SPSS statistical bag to derive the following values: arithmetic mean, standard deviation and simple correlation coefficient. The researcher reached the most important conclusions: There is no statistically significant relationship between the forms of speed in the players of Al-Zawra Club. Finally he recommended preparing of a training curriculum to develop forms of speed for football players and paying attention to the preparation stage, especially the special preparation by emphasizing the importance of physical and skill preparation in the vocabulary of the training program